Construction of Convergent Sequence in Cone 2-Normed Spaces - Sadjidon, Sadjidon; Yunus , Mahmud; Sunarsini, Sunarsini ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2015)
We introduce an idea of convergent sequence in a cone 2-normed space. We show that the convergence in 2-normed spaces using the definition of 2-norm by considering its dual space. Then we construct the convergence in cone 2-normed space, particularly for l2-space.